Plant based diet and cardio metabolic risk profile in African population - Lopes, Tatum (Stellenbosch : Stellenbosch University, 2023)
Lopes, Tatum. 2024. Plant based diet and cardio metabolic risk profile in African population. Unpublished doctoral dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/1e3c5697-462c-4f5d-bec4-34d123ef54fd